Catalytic aquathermolysis of Shengli heavy crude oil with an amphiphilic cobalt catalyst - Cao, Yan-Bin; Zhang, Long-Li; Xia, Dao-Hong (Petroleum science, 2016)
An interfacially active cobalt complex,cobalt dodecylbenzenesulfonate,was synthesized.Elemental analysis,atomic absorption spectroscopy,Fourier transform infrared spectroscopy（FT-IR）,thermogravimetric analysis,and surface/interfacial tension determination were performed to investigate the properties of the catalyst.Results showed that the synthesized catalyst showed active interfacial behavior,decreasing the surface tension and interfacial tension between heavy oil and liquid phase to below 30 and 1.5 mN/m,respectively.The catalyst was not thermally degraded at a temperature of 400 ℃,indicating its high thermal stability.Catalytic performance of the catalyst was evaluated by carrying out aquathermolysis.The viscosity determination showed that the viscosity of the heavy oil decreased by 38%.The average molecular weight,group compositions,and average molecular structure of various samples were analyzed using elemental analysis,FT-IR,electrospray ionization Fourier transform ion cyclotron resonance（ESI FT-ICR MS）,and ～1H nuclear magnetic resonance.Results indicated that the catalyst could attack the sulfur- and O_2-type heteroatomic compounds in asphaltene and resin,especially the compounds with aromatic structure,leading to a decrease in the molecular weight and then the reduction in the viscosity of heavy oil.Therefore,the synthesized catalyst might find an application in catalytic aquathermolysis of heavy oil,especially for the high-aromaticity heavy oil with high oxygen content.